Multiple Hamartoma Syndrome with Characteristic Oral and Cutaneous Manifestations - Prashanthi Chippagiri; Spoorthi Banavar Ravi; Neha Patwa (Hindawi Limited, 2013)
Aim. To present a case of Cowden's syndrome and emphasize the importance of continued cancer surveillance in these patients. Cowden syndrome is an inherited autosomal dominant trait with incomplete penetrance and a range of expressivity. It is characterized by multiple hamartomas and neoplasms. Mucocutaneous features include trichilemmomas, oral mucosal papillomatosis, acral keratosis, and palmoplantar keratosis. Here, we report a case of Cowdens syndrome of a 30-year-old female patient who came with a complaint of multiple growths in the oral cavity of a three-month duration. On examination, multiple skin-colored, flat-topped papules over her forehead and right malar bone and multiple papillomatous papules involving all the mucosal surfaces intraorally were observed. This syndrome is associated with the development of several types of malignancies, especially breast carcinoma and thyroid carcinoma, which is why early recognition and regular and vigilant surveillance of individuals with the syndrome are important.